The Red Sea: The Formation, Morphology, Oceanography and Environment of a Young Ocean Basin - Rasul, Najeeb M.A (Springer, 2015)
This book presents a broad overview of the current state of knowledge regarding the Red Sea, from its geological formation and oceanographic development to the environmental influences on its ecology and the changes it is experiencing due to the rapid development of its coastlines and role as one of the world’s major transport routes. The book gathers invited contributions from researchers with an interest in the geology, geophysics, oceanography and environment of the Red Sea, while also providing comprehensive new data and a complete review of the literature. It will be of interest not only to researchers actively studying the sea and its surroundings, but will also appeal to all those involved in planning and managing the Red Sea, its environment, its resources and the countries which rely on its existence